La política de parques y ciudades industriales en México: etapa experimental, 1953-1970 - Garza Villarreal, Gustavo (El Colegio de México A.C., 1988)
From 1953 to 1986, one hundred and thirty industrial parks and cities have been built in Mexico, marking one of the most significant measures taken to promote industrialization in backward zones and to attempt to prevent high rates of industrial concentration in Mexico City, Monterrey, and Guadalajara. The development of this system of industrial parks and cities can be broken down into two major stages: i) the experimental stage, 1953- 1970, and ii) the stage of expansion, 1971-1987. Within such a framework, the author of this article analyzes the general features of the experimental stage of this system in order to assess its results, and will consider the stage of expansion in the subsequent phase of the project of which this article forms part.